Introduction - The Historical Review, (The Historical Review/La Revue Historique, 2022)
Philhellenism has been one of the research fields of the Institute of Historical Research since its very creation. The relevant inquiries were initiated in 1960 by Loukia Droulia (1931–2019), who devoted much of her work on the issue, dedicated her thesis to it (1974) and compiled the bibliography of philhellenism, which remains the basic research tool for studies on the subject (1st ed. 1974; 2nd rev. ed. 2017). Therefore, it was due and expected that philhellenism would form part of the Institute’s academic activities during the bicentenary of the outbreak of the Greek War of Independence (1821). In October 2021 in Athens, the Institute organised an international conference on “National Movements and Philhellenism”, the proceedings of which are due to be published in Greek in 2022.